Pentingnya Transformasi Digital UMKM dalam Pengembangan Ekonomi Indonesia - Enny Diah Astuti; Rahmi Rosita (Institut Nalanda, 2024)
UMKM are small and medium enterprises in Indonesia. Digital transformation is very important for the success of UMKM in Indonesia. With technological advancements, businesses must adapt and adopt digital solutions to remain competitive in the global market. The integration of digital solutions into operational systems allows businesses to manage processes, expand their customer base, and enhance efficiency. This not only benefits individual businesses but also contributes to the sustainable economic growth of the country. The objective of the research on the digital transformation of UMKM will contribute to job creation, innovation, and overall economic growth. This comprehensive research approach will not only explain the current status of digitalization among UMKM in Indonesia but also provide valuable recommendations for policymakers, business owners, and other stakeholders on how to support and promote further digital transformation in this sector. By understanding the impact of digital skills training programs and identifying potential challenges, strategies can be developed to address these issues and ensure the sustainable growth of UMKM in the digital era. Ultimately, this research has the potential to drive innovation, enhance competitiveness, and ultimately contribute to the overall economic development of Indonesia.